The impact of crude oil prices, interest rates, and the Rupiah exchange rate on the transportation and logistics sector stock index (IDX-TRANS), 2021–2025 - Dias Febriansyah Subekti; Joy Elly Tulung; Priskila Bernita Rottie (The Contrarian : Finance, Accounting, and Business Research, 2026)
This study examines the impact of crude oil prices, interest rates, and the Rupiah exchange rate on the Transportation and Logistics Sector Stock Index (IDX-TRANS) on the Indonesia Stock Exchange for the period 2021–2025. Unlike prior sectoral studies that model a narrower set of macroeconomic drivers of IDX-TRANS, this study extends the specification by incorporating the BI Rate as an additional systematic risk factor and by explicitly controlling for the structural break associated with the COVID-19 mobility-restriction (PPKM) period. Grounded in Arbitrage Pricing Theory (APT) and the Efficient Market Hypothesis (EMH), this research employs a quantitative causal design using 59 monthly time-series observations (reduced from a nominal 60 months due to first-differencing). Variables are transformed into growth rates and first differences to satisfy stationarity requirements, confirmed using the Augmented Dickey-Fuller (ADF) test. Multiple linear regression analysis is conducted with inflation and a PPKM policy dummy as control variables, and classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity) confirm that the model satisfies Best Linear Unbiased Estimator (BLUE) criteria. The simultaneous test (F-test) confirms that all variables jointly and significantly affect IDX-TRANS movements (Prob > F = 0.0062). Partially, interest rates (BI Rate) exert a significant negative effect (coefficient = −13.3604; p = 0.021), and the Rupiah exchange rate also has a significant negative effect (coefficient = −1.7850; p = 0.027), while crude oil prices show no significant effect (p = 0.547), attributed to the pass-through effect mechanism. The model explains 18.79% of IDX-TRANS variation (Adjusted R² = 0.1879). These findings suggest that monetary policy tightening and currency depreciation pose the greatest systemic risks to capital-intensive transportation firms in Indonesia.